Predicting effect of Personality Traits and Age on Emotional Intelligence (Indian Journal of Public Health Research & Development, 2020)
People who have high emotional intelligence create understanding or know how to manage their ownemotions and they know how to read emotions of others. Emotional intelligence was positively connectedto physical, psychosomatic and mental health. The studies on the predictors of emotional intelligence,particularly in India are limited. For this purpose focus of the present study was to investigate the predictingeffect of personality traits (neuroticism & extraversion) on emotional intelligence among the student ofRaipur, India. A sample of the study comprised 300 P.G. students (male=50; female=50). Mangal EmotionalIntelligence Inventory and Eysenck’s Maudsley Personality inventory (M. P. I.) were used to measuringemotional intelligence (EI) and personality traits. SPSS 16th version, structure equation model (SEM) withADANCO, jamovi. (Version 1.0) were used for analysis. Measurement model was excellent fit in the samples[CFI = .968, TLI=0.904, SRMR=.033 and RMSEA = 0.11 (RMSEA 90% CI: Lower-0.0495, Upper-0.189)].The findings revealed that personality traits, neuroticism emerged as significant predictors of emotionalintelligent, intra personal awareness, inter personal awareness and inter personal management. Age emergedas significant predictors of emotional intelligent and its dimension. The findings also revealed that genderand extraversion have no impact on emotional intelligent and its dimension. A stable personality, age andtheir psychological wellbeing are important in enhancing the emotional intelligence of young students asthere is a possibility in improving their emotional intelligence.
Keywords: Emotional Intelligence, Neuroticism, Extraversion, Structure equation model.